2016
DOI: 10.1016/j.jtcvs.2015.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass grafting improves short-term outcomes in high-risk patients compared with on-pump coronary artery bypass grafting: Meta-analysis

Abstract: OPCAB is associated with a significant reduction in the odds of cerebral stroke compared with conventional CABG. In addition, benefits of OPCAB in terms of death, MI, and cerebral stroke are significantly related to patient risk profile, suggesting that OPCAB should be strongly considered in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 129 publications
6
132
0
14
Order By: Relevance
“…A further effort in minimizing the occurrence of some complications related to conventional CABG has led to the development of the off‐pump (OPCAB) technique in which the anastomoses are performed on the beating heart 4. Observational studies have suggested that, by avoiding the negative effects of CBP, OPCAB may substantially reduce the rate of mortality and morbidity when compared with conventional CABG 30, 31 and in particular in high‐risk patients 5, 32. Standard OPCAB, however, still requires application of a side biting clamp to complete proximal anastomoses, thus increasing the risk of dislodging fragile material from the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…A further effort in minimizing the occurrence of some complications related to conventional CABG has led to the development of the off‐pump (OPCAB) technique in which the anastomoses are performed on the beating heart 4. Observational studies have suggested that, by avoiding the negative effects of CBP, OPCAB may substantially reduce the rate of mortality and morbidity when compared with conventional CABG 30, 31 and in particular in high‐risk patients 5, 32. Standard OPCAB, however, still requires application of a side biting clamp to complete proximal anastomoses, thus increasing the risk of dislodging fragile material from the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Deppe et al in meta-analysis of RCTs on almost 16,900 patients found no difference in 30-day mortality. Kowalewski et al in meta-analysis of over 19,000 patients demonstrated no significant difference in short term mortality (1). The evidence is summarised in Table 1.…”
Section: Operative Mortalitymentioning
confidence: 97%
“…OPCAB, off-pump coronary artery bypass; ONCAB, on-pump coronary artery bypass; RCT, randomized controlled trial; CI, confidence interval; RR, relative risk. (1,3) found no difference in myocardial infraction rates between ONCAB or OPCAB. In the meta-analysis by Deppe et al (3), the incidence of low cardiac output and infection were reduced with use off-pump.…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 97%
See 2 more Smart Citations